The Role of Human Resource Management in Preparing Organizations for Transformation in The 4.0 Era - Wahyudi, Tri Nur; Anggorowati, Luki Sri; Wajdi, M. Farid (Proceedings International Conference on Education Innovation and Social Science, 2025)
The Industrial Era 4.0 has brought major changes in various aspects of organizations, including how human resource management (HR) plays a role in preparing for digital transformation. This research aims to analyze the role of human resource management in preparing organizations for transformation in the 4.0 era. The type of research is qualitative, using the literature study method. The data sources come from journals and books related to HR management and transformation in the 4.0 era. The data analysis technique uses thematic analysis from the data source. The research results show that the role of HRM is in preparing organizations for transformation in the 4.0 era including as a strategic partner for organizational transformation, developing workforce digital competency, utilizing HR technology for process efficiency, transformational leadership as a driver of change, creating a culture of innovation and collaboration, flexibility in workforce management, managing resistance to change, data-based performance management, increasing engagement and employee satisfaction, and achieving organizational sustainability.